Physicochemical, Functional, Fatty Acids Profile, Health Lipid Indices, Microstructure and Sensory Characteristics of Walnut-Processed Cheeses - Khaled A. Abbas; Hani S. Abdelmontaleb; Shaimaa M. Hamdy; Abderrahmane Aït-Kaddour (Foods, 2021)
In the present study, processed cheeses fortified with walnut paste (a high source of omega-3 fatty acids) were developed and characterized. In order to identify the best cheese formulation, the effects of different proportions of walnut paste (0, 5, 10, and 15%) on cheese physicochemical, functional, fatty acids profile, health lipid indices (atherogenic and thrombogenic), microstructure, and sensorial characteristics were studied. Results showed that walnut-added samples had significantly (p ≤ 0.05) higher levels of acidity, protein, fat, and ash contents with lower meltability and oil separation index compared to the control. Processed cheeses with walnuts contained significantly (p ≤ 0.05) higher percentages of MUFAs, and ω-3 PUFAs (mainly α-linolenic acid) and significantly (p ≤ 0.05) lower amounts of SFAs (mainly myristic, palmitic and stearic acids) and ω6/ω3 ratio. Scanning Electron Micrograph of processed cheese containing walnut paste showed uniform distribution of walnut in the protein matrix. Processed cheeses made with 5 or 10% walnut paste presented the most acceptable sensory properties. These results indicated that walnut paste supplementation can be used as a nutritional strategy to increase concentrations of human health-promoting fatty acids in processed cheeses while maintaining good sensory and technological properties.